Writing Game Center apps in iOS - Nahavandipoor, Vandad (O'Reilly, 2011)
Now that Apple has introduced the GameKit framework to its iOS SDK, you can integrate Game Center features directly into your iPhone and iPad apps. This concise cookbook shows you how it's done, with 18 targeted recipes for adding leaderboards, user authentication, achievements, multiplayer games, and many other features. How do you display players' scores and achievements? How do you create Game Center accounts and add friends? Each recipe in this book includes a simple code solution you can put to work immediately, along with a detailed discussion that offers insight into why and how the recipe works. Recipes include techniques to: Set up Game Center for an iOS App Use block objects and Grand Central Dispatch to write Game Center apps Authenticate a local player in Game Center Use iTunes Connect to create leaderboards and achievements Retrieve leaderboard and achievement information programmatically Handle players' state changes in multiplayer games.